Gut Microbiota Modulation by Phytobiotics in Pacific White Shrimp (Litopenaeus Vannamei): A Literature Review - Permatasari, Sheny (Applied Research in Science and Technology, 2026)
Background: The Pacific white shrimp (Litopenaeus vannamei) is one of the most economically important aquaculture species worldwide. However, intensive farming practices have increased the incidence of disease outbreaks, environmental stress, and gut microbiota dysbiosis, resulting in reduced productivity and sustainability. Phytobiotics have emerged as promising natural feed additives due to their antimicrobial, antioxidant, and immunostimulatory properties, with increasing evidence suggesting their role in modulating gut microbial communities. Nevertheless, current findings remain fragmented across different phytobiotic sources and experimental approaches.Aims: This systematic literature review aimed to synthesize current evidence regarding the effects of phytobiotics on gut microbiota composition, growth performance, immune responses, and disease resistance in L. vannamei.Methods: Literature published between 2015 and 2025 was retrieved from Scopus, ScienceDirect, and Google Scholar following predefined inclusion criteria, and 20 eligible studies were included in the qualitative synthesis.Results: The reviewed studies consistently demonstrated that phytobiotics promote beneficial gut bacteria while suppressing opportunistic pathogens, particularly Vibrio spp., thereby improving intestinal microbial balance and hepatopancreatic health. These microbial changes were associated with enhanced nutrient utilization, improved feed efficiency, stronger innate immune responses, increased antioxidant capacity, and greater resistance to bacterial infections, ultimately resulting in better growth performance. Although the available evidence supports the potential of phytobiotics as sustainable alternatives to antibiotics, microbiome-based studies remain limited. Future research integrating high-throughput sequencing and multi-omics approaches is required to elucidate the mechanisms underlying phytobiotic–microbiota interactions and optimize their application in sustainable shrimp aquaculture.